METHOD FOR ENHANCING FMECA (XMECA) SAFETY ASSESSMENT PROCEDURES CONSIDERING THE CRITICALITY OF ASSUMPTIONS AND ANALYSIS ERRORS (Computer systems and information technologies, 2025)
In existing studies that discuss the Failure Modes, Effects, and Criticality Analysis (FMECA, XMECA) method, two principal limiting factors are commonly identified: the significant influence of engineers’ and auditors’ experience on the resulting safety assessments, and the presence of restrictive assumptions embedded in assessment procedures and supporting tools. To address these limitations, this paper proposes a method for enhancing FMECA (XMECA) safety assessment procedures that explicitly accounts for the criticality of underlying assumptions and analysis errors. Case study of applying the proposed method demonstrate that it can serve as an effective instrument for researchers and developers working on reliability and safety assessment problems in critical systems. Further research is devoted to application of the method in different contexts and industrial sectors.
Keywords: safety assessment; assumption; criticality; FMECA; XMECA